Hydrogen recovery from H2S-CH4 inclusions trapped in quartz triggered by green laser-induced photolysis of polysulphane-sulphur bonds. (July 2019) - Hurai, Vratislav; Černušák, Ivan; Randive, Kirtikumar
Abstract: Natural H2 S-CH4 inclusions enclosed in quartz were transformed into H2 -CH4 mixture with none or negligible H2 S concentration after short irradiation of associated sulphur daughter phase with 532 nm photons emitted by a 25 mW Nd-YAG laser. As much as 57 mol. % (73.8 wt %) H2 S in the gas inclusions was converted to its constituent elements in sulphur-bearing inclusions. In contrast, the H2 S splitting did not occur within the inclusions devoid of the sulphur daughter phase. Raman spectroscopic data and density functional theory-based calculations corroborated the existence and photolytic breakdown of sulphur-bound polysulphanes, which provided accelerated H ⋅ radicals capable of breaking the stronger S-H bond in the surrounding molecular H2 S at room temperature. The polysulphane-supported photolysis combines benefits of deactivation of the toxic and corrosive H2 S pollutant with hydrogen and sulphur recovery, and as such it has a potential of utilizing for the environment-friendly processing and purification of the super-soar natural gas. Highlights: Conversion of H2 S-CH4 to H2 -CH4 mixture achieved by the illumination of photo-activated sulphur with green laser. Natural origin of photo-activated sulphur by the dissolution of polysulphanes in the sulphur melt. Raman spectroscopy combined with DFT calculations reveal polysulphane-sulphur bonds in the photo-activated sulphur. Possibly new method of hydrogen recovery from sub-quality natural gas extremely enriched in hydrogen sulphide.